2019
DOI: 10.1371/journal.pone.0223527
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the characteristics of acute primary angle closure in Korea over the past 10-years

Abstract: PurposeTo investigate the changes in the demographic, clinical, and biometric characteristics of APAC patients in South Korea during the last decade.MethodsMedical records of patients with APAC who visit the emergency department or the glaucoma clinic of Chonnam National University Hospital, a tertiary referral center in Gwangju, South Korea in 2007 and 2017 were analyzed. Demographics, clinical characteristics, and treatment modality were compared between the APAC patients in 2007 and 2017.ResultsThe number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…The median age of our four ACG patients was 69.5 years, and the women to men ratio was 3:1, similar to that in a multi-centered Korean study with an average age of 64.28 years and sex ratio of 3.13:1 [ 26 ]. Axial lengths of our ACG subjects were 21.84 mm, 22.95 mm, 22.37 mm, and 23.71 mm, which were similar with average 22.42 mm in one of acute primary angle-closure studies in Korea [ 27 ]. Conversely, our subjects’ anterior chamber depths (ACDs) were 2.19 mm, 2.19 mm, 2.89 mm, and 2.31 mm, which were deeper than the average ACDs in ACG cases in Korea (1.87 mm) in 2017 [ 27 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The median age of our four ACG patients was 69.5 years, and the women to men ratio was 3:1, similar to that in a multi-centered Korean study with an average age of 64.28 years and sex ratio of 3.13:1 [ 26 ]. Axial lengths of our ACG subjects were 21.84 mm, 22.95 mm, 22.37 mm, and 23.71 mm, which were similar with average 22.42 mm in one of acute primary angle-closure studies in Korea [ 27 ]. Conversely, our subjects’ anterior chamber depths (ACDs) were 2.19 mm, 2.19 mm, 2.89 mm, and 2.31 mm, which were deeper than the average ACDs in ACG cases in Korea (1.87 mm) in 2017 [ 27 ].…”
Section: Discussionsupporting
confidence: 73%
“…Axial lengths of our ACG subjects were 21.84 mm, 22.95 mm, 22.37 mm, and 23.71 mm, which were similar with average 22.42 mm in one of acute primary angle-closure studies in Korea [ 27 ]. Conversely, our subjects’ anterior chamber depths (ACDs) were 2.19 mm, 2.19 mm, 2.89 mm, and 2.31 mm, which were deeper than the average ACDs in ACG cases in Korea (1.87 mm) in 2017 [ 27 ].…”
Section: Discussionsupporting
confidence: 73%
“…Additionally, these data are very similar to those of previous reports in China or Korea in the non-pandemic period. 26,[35][36][37] However, the time from symptoms to treatment in the pandemic group was 7.92 ± 6.14 days, which was significantly longer than that in the control group (3.63 ± 2.93 days). In the pandemic group, the time from symptoms to treatment in COVID-19-positive patients was 8.42 ± 6.21 days, which was longer than that in COVID-19-negative patients (6.55 ± 5.76 days).…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies have reported that the AC mechanism involved in most AAC eyes and fellow eyes of AAC is predominantly PB, while non‐pupillary block or multiple mechanisms have a greater role in non‐acute presentations (Barkan 1954 ; Zhou et al 1993 ; Moghimi et al 2018 ). Acute angle‐closure (AAC) is a subtype of PACD and an ocular emergency which in the absence of timely treatment causes permanent visual loss (Ha et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%